The Bright Side of Youth: A Literature Review on Optimism and It’s Psychological Benefits for Anxious Among Young Adults - Alfina Saskia Ananda; Lussy Dwiutami Wahyuni; Anna Armeini Rangkuti; Zarina Akbar (International Conference on Psychology and Education (ICPE), 2025)
The topic of optimism and anxiety among young adults is quite often discussed. Previous studies explain that optimism plays an active role in reducing a person's anxiety levels, especially in young adults. However, several studies show that optimism has no influence whatsoever in the process of reducing anxiety. This article then presents identifying the dynamics of the influence of optimism on anxiety in young adults, which is reviewed from various perspectives of previous research. This article also aims to determine the role of optimism as a protector for reducing anxiety levels among young adults. The method used in this study was to review the literature by conducting a review process of 20 articles obtained through the search process with Google Scholar and Scopus. The results of the study showed that optimism was proven to have a protective role among young adults in overcoming anxiety. Optimism also has an important role in reducing anxiety levels among young adults.